An investigation of the stability of meropenem in elastomeric infusion devices - Foy, F.; Luna, G.; Martinez, Jorge; Nizich, Z.; Seet, J.; Lie, K.; Sunderland, Bruce; Czarniak, Petra (2019)
Purpose: To evaluate the stability of meropenem trihydrate in elastomeric infusion devices at a range of selected concentrations (6, 12, 20 and 25 mg/mL) at ambient, refrigeration and freezing temperatures. Methods: Meropenem Ranbaxy® (meropenem trihydrate equivalent to anhydrous meropenem 1 g) vials for injection were reconstituted with 0.9% sodium chloride and adjusted to pH 6.5 using 1 M hydrochloric acid. Following preparation, solutions were stored for 7 days at either 6.7°C in elastomeric infusion devices or at −19°C in glass vials; samples of each concentration were removed from the infusion devices at specific time-points and stored for 24 hrs at 22.5°C. All solutions were assayed at specific time-points using high-performance liquid chromatography. Forced degradation in hydrochloric acid, sodium hydroxide and hydrogen peroxide was carried out at 40°C. Results: The lowest concentration of meropenem (6 mg/mL) displayed the highest stability. It maintained >90% of its initial concentration for up to 144 hrs when stored at 6.7°C and 72 hrs following 24 hrs storage at 22.5°C, having been initially refrigerated for 48 hrs. Meropenem 20 mg/mL required immediate administration following preparation under ambient temperatures, whilst meropenem 25 mg/mL did not remain stable following 24 hrs storage at ambient temperatures. Frozen meropenem solutions displayed good stability in all concentrations but were physically unstable due to the formation of a precipitate. Conclusion: At lower concentrations, meropenem showed suitable stability for storage and administration in elastomeric infusion devices, at refrigerated temperatures. To enhance the stability of lower concentration solutions when exposed to ambient temperatures by ambulatory patients, a more adept method of maintaining lower temperatures that reflect refrigerated conditions for elastomeric infusion devices should be devised.